2015
DOI: 10.1245/s10434-015-4739-1
|View full text |Cite
|
Sign up to set email alerts
|

Overall Survival, Disease-Free Survival, Local Recurrence, and Nipple–Areolar Recurrence in the Setting of Nipple-Sparing Mastectomy: A Meta-Analysis and Systematic Review

Abstract: This study did not detect adverse oncologic outcomes of NSM in carefully selected women with early-stage breast cancer. Use of prospective data registries, notably the Nipple-Sparing Mastectomy Registry, will add clarity to this important clinical question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
133
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(141 citation statements)
references
References 26 publications
5
133
1
2
Order By: Relevance
“…Over the years, a number of prospective and retrospective studies have demonstrated a cancer recurrence rate in the NAC of up to 2%, with local recurrence rates ranging from 1-6% (17)(18)(19). A more recent meta-analysis comparing NSM to skin-sparing mastectomy (SSM) and/or modified radical mastectomy (MRM) identified no difference in overall survival, disease free survival or local recurrence amongst the groups in properly selected patients with early stage breast cancer (20).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, a number of prospective and retrospective studies have demonstrated a cancer recurrence rate in the NAC of up to 2%, with local recurrence rates ranging from 1-6% (17)(18)(19). A more recent meta-analysis comparing NSM to skin-sparing mastectomy (SSM) and/or modified radical mastectomy (MRM) identified no difference in overall survival, disease free survival or local recurrence amongst the groups in properly selected patients with early stage breast cancer (20).…”
Section: Introductionmentioning
confidence: 99%
“…Nipple-sparing mastectomy (NSM), which has emerged as an alternative to standard mastectomy, is felt to be oncologically safe, provides cosmetic and quality-of-life benefits for patients, and results in a reduced need for additional nipple reconstruction procedures (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, one of the frequent complications following NSM is nipple-areola complex (NAC) and skin flap ischemia and necrosis, the rate of which varies from 0 to 48%, with most series reporting rates of 10-15% (1, 3, 4, 6-9, 11, 13-25).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Autologous reconstruction in NSM is a safe and effective option that achieves an aesthetic, natural-appearing breast in a single stage. 14,15 However, patients undergoing NSM may be more likely to have a low BMI with a paucity of adequate donor site tissue for reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest similar recurrence rates with NSM compared with traditional mastectomy techniques. [1][2][3][4][5][6] Moreover, NSM has been demonstrated in multiple studies to be a safe and effective procedure from a reconstructive perspective, with acceptably low rates of NAC necrosis among other complications. [7][8][9][10][11][12] As the indications for NSM continue to be established, the popularity of this procedure has risen among both patients and surgeons.…”
mentioning
confidence: 99%